The Process-Property-Performance Relationship of Medicated Nanoparticles Prepared by Modified Coaxial Electrospraying - Weidong Huang; Yuan Hou; Xinyi Lu; Ziyun Gong; Yaoyao Yang; Xiao-Ju Lu; Xian-Li Liu; Deng-Guang Yu (MDPI AG, 2019)
In pharmaceutical nanotechnology, the intentional manipulation of working processes to fabricate nanoproducts with suitable properties for achieving the desired functional performances is highly sought after. The following paper aims to detail how a modified coaxial electrospraying has been developed to create ibuprofen-loaded hydroxypropyl methylcellulose nanoparticles for improving the drug dissolution rate. During the working processes, a key parameter, i.e., the spreading angle of atomization region (θ, °), could provide a linkage among the working process, the property of generated nanoparticles and their functional performance. Compared with the applied voltage (V, kV; D = 2713 − 82V with RθV2 = 0.9623), θ could provide a better correlation with the diameter of resultant nanoparticles (D, nm; D = 1096 − 5θ with RDθ2 = 0.9905), suggesting a usefulness of accurately predicting the nanoparticle diameter. The drug released from the electrosprayed nanoparticles involved both erosion and diffusion mechanisms. A univariate quadratic equation between the time of releasing 95% of the loaded drug (t, min) and D (t = 38.7 + 0.097D − 4.838 × 105D2 with a R2 value of 0.9976) suggests that the nanoparticle diameter has a profound influence on the drug release performance. The clear process-property-performance relationship should be useful for optimizing the electrospraying process, and in turn for achieving the desired medicated nanoparticles.